Implementasi Adaptive Neuro Fuzzy Inference System (ANFIS) Dalam Memprediksi Penjualan Roti Kacang - Ega Widya Sari; Agus Perdana Windarto; Rizki Alfadillah Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Sales is an effort or concrete steps taken to move a product, whether in the form of goods or services, from producers to consumers as the target. The main purpose of sales is to bring in profits or profits from products or goods produced by producers with good management. Prediction of sales of goods is one way to maintain the stability of sales of goods, the prediction results obtained can be taken into consideration for making decisions in business management planning. Prediction is done to find out the forecast of future sales, to meet consumer needs. One of the problem solving methods used in this research is the Adaptive Neuro Fuzzy Inference System (ANFIS). ANFIS is a method that uses a Neural Network to implement a Fuzzy Inference System. By using the ANFIS method as a solution for solving the case of prediction of peanut bread sales in the future so that the prediction results can be input to UD. Family in order to provide production stock in accordance with the predictions made and can increase sales of peanut bread at UD.Family optimally